2013
DOI: 10.1038/srep02169
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of hierarchical MoSx/CNT nanocomposites (2<x<3): towards high performance anode materials for lithium ion batteries

Abstract: Two dimension (2D) layered molybdenum disulfide (MoS2) has emerged as a promising candidate for the anode material in lithium ion batteries (LIBs). Herein, 2D MoSx (2 ≤ x ≤ 3) nanosheet-coated 1D multiwall carbon nanotubes (MWNTs) nanocomposites with hierarchical architecture were synthesized via a high-throughput solvent thermal method under low temperature at 200°C. The unique hierarchical nanostructures with MWNTs backbone and nanosheets of MoSx have significantly promoted the electrode performance in LIBs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(178 citation statements)
references
References 53 publications
8
170
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28] Similar approaches involve mixing MoS2 with polyaniline nanowires 29 or carbon nanotubes. 19,[30][31][32] 3 However, the composite electrodes described above remain far from optimised as LIB electrodes. Although such approaches generally result in good capacity and improved stability, the rate capability is still not as good as had been hoped.…”
Section: Abstract: Advances In Lithium Ion Batteries Would Facilitatementioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27][28] Similar approaches involve mixing MoS2 with polyaniline nanowires 29 or carbon nanotubes. 19,[30][31][32] 3 However, the composite electrodes described above remain far from optimised as LIB electrodes. Although such approaches generally result in good capacity and improved stability, the rate capability is still not as good as had been hoped.…”
Section: Abstract: Advances In Lithium Ion Batteries Would Facilitatementioning
confidence: 99%
“…Electrode materials were then mixed with polyacrylic acid (as the binder) in 9:1 weight ratio and dispersed in H2O to form a homogeneous slurry. Subsequently, the slurry was uniformly applied onto a Cu foil, and vacuum dried at 25,27,28,67,68 and MoS2/NT (triangles) [30][31][32] electrodes. The filled stars represent our capacity data (extracted from rate data for the 20 wt% composite), normalised to the total anode…”
Section: Battery Electrode Preparationmentioning
confidence: 99%
“…Raman peaks of MoS 2 centered at 380.5 and 405.7 cm −1 correspond to the in-plane (E 2g ) and out-of-plane Mo-S phonon mode (A 1g ) of typical MoS 2 -layered structure, respectively [50]. It is found that the ratio of A 1g /E 2g of MoS 2 dramatically decrease after the transformation of Ni(OH) 2 into NiSe, further suggesting the increase of the edge defects [51]. What's more, the wavenumber of A 1g peak became smaller after the tearing.…”
Section: Resultsmentioning
confidence: 86%
“…It also attracts prime attention as an auxiliary power source to secondary batteries because of fast charging/discharging capability, high power density, and excellent cyclability as shown in Figure 10. 185 Recent studies demonstrate that MoS 2 nanosheets prepared by hydrothermal method and by exfoliation act as a promising typical pseudocapacitive material for supercapacitor application 184,186 . Having advantages of high conductivity and high surface area, metallic VS 2 nanosheets have been employed to fabricate in plane supercapacitor electrodes 187 .…”
Section: Canadian Chemical Transactionsmentioning
confidence: 99%